Dampak Medioker di Era Jokowi-Jk terhadap Welfare State Berdasarkan UU No. 17 Tahun 2007 tentang RPJP Nasional - Maulida Maulaya Hubbah (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
President Joko Widodo and his deputy Jusuf Kalla after being inaugurated to form and inaugurate his cabinet on October 27, 2014, however, there are several names of ministers whose capacity is still in doubt, because they still involve ministers indicated in corruption cases as reported by the People's Decree Movement and the Civil Coalition to the Commission Corruption Eradication (KPK). Therefore, in the end, it raises public concern regarding its work ethic which will have an impact on the vision of the welfare state of the Indonesian State based on Law Number 17 of 2007 concerning the National Long-Term Development Plan (RPJPN). The focus of the problems examined in this thesis are 1). How is the process of preparing the Cabinet for the Jokowi-JK era for the 2014-2019 period. 2). What is the mediocre impact of the Jokowi-JK administration on the vision of the welfare state based on Law Number 17 of 2007 concerning the National Long-Term Development Plan (RPJPN)? This research is carried out by reviewing and examining written sources relevant to the object of discussion so that clear data can be obtained, the object of study includes basic norms or rules, legal principles, laws, and regulations so that it is termed normative legal research. or also known as library law research, library research.